Factors related to air pollution and impacts on respiratory health in Malaysia - Zainib Amirah Anwar; Safirah Jaan Jaafar; Abdul Rahman Ramdzan (Universiti Malaysia Sabah, 2024)
Introduction: Air pollution, driven by urbanization, industrial activities, and transboundary haze, poses a significant threat to public health in Malaysia. It contributes to respiratory diseases such as asthma, chronic obstructive pulmonary disease (COPD), and bronchitis. Although advancements in monitoring have improved data accuracy, challenges remain in addressing regional disparities and climate-related factors. This review aims to explore air quality monitoring, factors influencing pollution, and its impacts on respiratory health in Malaysia. Objective: To identify the scope of air quality monitoring, factors contributing to air pollution, and the associated impacts on respiratory health in Malaysia. Method: A scoping review methodology was employed, using databases such as ScienceDirect, Scopus, and Google Scholar. Studies were included if they were conducted in Malaysia, published in English within the last five years, and investigated the relationship between air pollution and respiratory diseases. Data extraction focused on pollutants, study settings, and key findings. Results: The review included 19 studies. Key findings indicate that urbanization, vehicular emissions, and transboundary haze are primary contributors to air pollution. Pollutants such as PM10, PM2.5, and NO2 are significantly associated with respiratory diseases, particularly asthma and COPD. Monitoring data shows that urban areas face greater challenges, while transboundary pollution affects rural and suburban regions. Conclusion: Air pollution remains a pressing issue in Malaysia, exacerbated by urbanization and transboundary haze. Strengthening air quality policies, enhancing monitoring systems, and promoting public awareness are crucial to reducing health risks. Future research should prioritize underrepresented regions, long-term health impacts, and the effectiveness of regulatory measures. Collaborative and region-specific interventions are essential to combat this multifaceted challenge.